Spillover effects of restatements on the financial reporting behavior of board-interlocked firms - CHEN, Chih-Ying (Institutional Knowledge at Singapore Management University, 2012)
This study examines the spillover effects of restatements on the financial reporting behavior of firms that share common directors with the restating firms (“interlocked firms”). Using a sample of restating firms, we find that restatements trigger investors’ concerns over the financial reporting among interlocked firms and these reporting concerns induce the directors associated with the restatement (“tainted directors”) to improve the financial reporting quality at the interlocked firms. Specifically, interlocked firms exhibit lower discretionary accruals in the year after the restatement events than do control firms, and this effect is more pronounced when the tainted directors also sit on the audit committees of the interlocked firms or when the tainted directors continue to serve in the interlocked firms in the year following the restatement. Our study extends the literature on the consequences of restatement and the governance implications of board interlocks.